Use of Biochar-peat Mixture to Reduce Odour from Animal Farms - Maarit Hellstedt (Сельскохозяйственные машины и технологии, 2019)
Abstract. Odour from agriculture causes local nuisance to the neighborhood. Litter and cover materials can be used in animal housing and in storage of manure to reduce the odour problem. The use of biochar as a covering for animal manures is a new innovation and enhances the possibility to minimize the emissions from animal farms. (Research purpose) To study the possibility of using a mixture of biochar and peat as a manure covering, in order to reduce the intensity of odor on livestock farms. (Materials and methods) The potential of a mixture of biochar and peat for the odour control was tested in a laboratory study. A 10 cm layer of fresh mink manure was placed on the bottom of a 5 liter test bucket and the manure was covered with biochar-peat mixture (mixed in 50/50 ratio by volume) using five different covering thicknesses. Uncovered manure was used as a reference. The odour emission was measured with an olfactometric method that is based on odour sensation of a person. Also the character of the odour was described. (Results and discussion) The results show that a biochar-peat covering of at least 3 cm is able to considerably reduce the odour from the manure. The character of the odour was at first peat-like for all covered buckets but with thin coverings it was changed to more manure-like after 2 days. The odour from buckets with thicker covers remained peat-like during the whole testing period. (Conclusion) It is recommended to apply a biochar-peat covering to neutralize ammonia and the unpleasant manure odour on livestock farms. The author has shown that the frequency of use and the thickness of a covering layer depend on the ambient temperature; therefore, it is not necessary to cover manure in winter.